2013
DOI: 10.1111/jftr.12021
|View full text |Cite
|
Sign up to set email alerts
|

Siblings of Individuals With Disabilities: Reframing the Literature Through a Bioecological Lens

Abstract: In the United States alone, there are almost 300,000 individuals with developmental disabilities. Researchers have focused primarily on such individuals and their parents; however, the developmental outcomes of such individuals' siblings have been understudied. Research on siblings frequently is atheoretical, which makes it difficult to organize findings in ways that enhance understanding of the multiple influences on sibling development and to predict and promote siblings' outcomes. Application of a theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 92 publications
1
20
0
Order By: Relevance
“…Fourth, this study identified mesosystem correlates of current sibling caregiving. Previous research had not examined any mesosystem contextual variables that may correlate with sibling caregiving status (Saxena & Adamsons, 2013). Thus, the current study extended the literature by identifying advocacy and future planning-mesosystem-level characteristics-were correlated with greater current sibling caregiving.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Fourth, this study identified mesosystem correlates of current sibling caregiving. Previous research had not examined any mesosystem contextual variables that may correlate with sibling caregiving status (Saxena & Adamsons, 2013). Thus, the current study extended the literature by identifying advocacy and future planning-mesosystem-level characteristics-were correlated with greater current sibling caregiving.…”
Section: Discussionmentioning
confidence: 62%
“…Previous research had not examined any mesosystem contextual variables that may correlate with sibling caregiving status (Saxena & Adamsons, 2013). Previous research had not examined any mesosystem contextual variables that may correlate with sibling caregiving status (Saxena & Adamsons, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although elements of the most proximal context—family--have been linked to TDSibs’ and/or ASDSibs’ individual adjustment, and in the face of theory, we still know relatively little about the effects of family processes on TD-ASD sibling relationships. Equally important are contexts beyond the family (e.g., local school and medical resources, state-level educational policies, sociocultural factors) that have implications for family and sibling dynamics (Saxena & Adamsons, 2013). Cultural values and practices are among the most significant but neglected such factors, although these may have significant implications ranging from effects on siblings’ activities and family roles to the degree of their interdependence across the lifespan (Weisner, 2002).…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Whilst such recent research does suggest that the field has moved away from its previous largely ‘atheoretical’ stance [9], there has been little attention given explicitly to synthesising theoretical frameworks from a wider standpoint that combines individual and broader system perspectives. Existing theoretically informed models are also not explicitly designed with a focus on sibling relationships [for an exception and comprehensive overview, see 10]. Many of the pathways shown in our framework have good empirical support, as discussed below, though others have been less thoroughly explored.
Fig.
…”
Section: A Framework To Continue Forward Momentum In Sibling Researchmentioning
confidence: 99%